The role of family in creating the ecological consciousness at children - Marković, Mirjana M (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2017)
Family as a community of parents and children has a great role in forming the ecological consciousness of children. It is the first social environment with witch child make contact, and it depends a lot of family what social habits child is going to adopt from his parents and what is going to be his attitude later about the nature and environment. The conditions of family life and especially in the first year of living are determinative for creating the consciousness and personality of the children. Family is not only the institution that does the socialisation, but also a factor of whom depends the personality the child is going to develop.